Extent Of Utilization Of Analytical Techniques And Susbsitantive Test By Accounting Staff For Fraud Detection In Large Scale Business Organisations In Delta State - Ezenwafor, J. I.; Udukeke, O. Frank (Advances in Social Sciences Research Journal, 2020)
This study on extent of utilization of analytical techniques and susbsitantive test by accounting staff for fraud detection in large scale business organisations in Delta State was necessitated by the growing incidence frauds that are crippling businesses and socio-economic development of the state. Two research questions guided the study and two null hypotheses were tested. Related literature to the study were reviewed. Descriptive survey research design was adopted for the study. The population of the study was 260 accounting staff. A sample size of 160 was drawn for the study using stratified sampling technique. A four-point rating scale questionnaire developed by the researchers containing 23 items in two clusters was used for data collection. Internal consistency method was used to determine the reliability of the questionnaire with Cronbach Alpha and this yielded reliability coefficient values of 0.91 and 0.84 respectively for the sections with an overall reliability of 0.88. Data were analyzed using mean and standard deviation to answer the research questions and determine the homogeneity of the respondents’ view while t-test and analysis of variance were used to test the hypotheses at 0.05 level of significance. The results showed that the accounting staff moderately utilized analytical technique for fraud detection but highly utilized substantive test. Furthermore, it was found that types and status of organization in NSE did not significantly influence the respondents’ ratings. Based on the findings of the study, it was concluded that the accounting staff are not adequately utilizing techniques that could facilitate fraud detection in large-scale business organisations as required to combact the menance. It was therefore recommended among others, that, management of LSBOs should sponsor their accounting staff on training and that sharesholders should insist that the techniques are adequately utilized by holding the management accountable for future incidence of fraud.